Akt Phosphorylation Influences Persistent Chlamydial Infection and Chlamydia-Induced Golgi Fragmentation Without Involving Rab14 - Huang, Xiaobao; Tan, Jinfeng; Chen, Xiaohong; Liu, Mingna; Zhu, Huiling; Li, Wenjing; He, Zhenjian; Han, Jiande; Ma, Chunguang (Frontiers in Cellular and Infection Microbiology, 2021)
Chlamydia trachomatis, as an obligate intracellular bacterium, cause multiple diseases involving the eyes, gastrointestinal tract, and genitourinary system. Previous researches confirmed that in acute chlamydial infection, C. trachomatis acquire essential lipids from the Golgi apparatus via Rab14-positive vesicle to support its survival and replication, while Akt phosphorylation participates in this process. However, the effects of Akt phosphorylation and Rab14 in persistent chlamydial infection remain unclear. Here, we discovered that the level of Akt phosphorylation was lower in persistent chlamydial infection, and positively correlated with the effect of activating the development of Chlamydia but did not change the infectivity. Rab14 exerted limited effect in persistent infection. Akt phosphorylation might regulate Chlamydia development and Chlamydia-induced Golgi fragmentation in persistent infection but not via Rab14. Our results indicated a new insight that Akt inhibitor could exert synergistic repressive effects with antibiotics in the persistent chlamydial infection induced by penicillin.